Watching a synapse grow: noninvasive confocal imaging of synaptic growth in Drosophila. - Zito, K.; Parnas, D.; Fetter, R.D.; Isacoff, E.Y.; Goodman, C.S. (Neuron, 1999)
The glutamatergic neuromuscular junction (NMJ) in Drosophila adds new boutons and branches during larval development. We generated transgenic fruit flies that express a novel green fluorescent membrane protein at the postsynaptic specialization, allowing for repeated noninvasive confocal imaging of synapses in live, developing larvae. As synapses grow, existing synaptic boutons stretch apart and new boutons insert between them; in addition, new boutons are added at the ends of existing strings of boutons. Some boutons are added de novo, while others bud from existing boutons. New branches form as multiple boutons bud from existing boutons. Nascent boutons contain active zones, T bars, and synaptic vesicles; we observe no specialized growth structures. Some new boutons exhibit a lower level of Fasciclin II, suggesting that the levels of this synaptic cell adhesion molecule vary locally during synaptic growth.